2009
DOI: 10.1016/j.nuclphysb.2008.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Constructing the supersymmetric Standard Model from intersecting D6-branes on theZ6orientifold

Abstract: Intersecting stacks of supersymmetric fractional branes on the Z ′ 6 orientifold may be used to construct the supersymmetric Standard Model. If a, b are the stacks that generate the SU (3) colour and SU (2) L gauge particles, then, in order to obtain just the chiral spectrum of the (supersymmetric) Standard Model (with non-zero Yukawa couplings to the Higgs mutiplets), it is necessary that the number of intersections a ∩ b of the stacks a and b, and the number of intersections a ∩ b ′ of a with the orientifold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 36 publications
3
50
1
Order By: Relevance
“…Simplest models include toroidal orbifold compactifications, see e.g., [75][76][77][78][79][80][81]. In this section we consider a type IIA orientifold of the…”
Section: An Explicit Examplementioning
confidence: 99%
“…Simplest models include toroidal orbifold compactifications, see e.g., [75][76][77][78][79][80][81]. In this section we consider a type IIA orientifold of the…”
Section: An Explicit Examplementioning
confidence: 99%
“…Most notably, by trial and error we found in earlier works that the existence of some Z 3 subsymmetry is favourable for providing three particle generations. For example, on the T 6 /(Z 4 × ΩR) [15] and T 6 /(Z 2 × Z 4 × ΩR) [16][17][18][19] backgrounds, it is impossible to construct globally defined supersymmetric D6-brane models with three quark generations, while on T 6 /(Z 6 × ΩR) [20,18,21,22] and T 6 /(Z 6 × ΩR) [23][24][25][26][27]22] such models have been obtained. For the latter, diverse investigations of the related low-energy effective field theory were performed in [22,[28][29][30][31], discrete remnants of gauge symmetries were first investigated in [32], and the relation to some Peccei-Quinn symmetry and axions was studied in [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24], and (T 2 ) 3 Γ with Abelian point groups Γ = Z N or Z N × Z M . In the latter case, models with all three-cycles inherited from the underlying torus have been constructed for Γ = Z 2 × Z 2 [25][26][27][28][29][30] and Z 2 × Z 4 [31][32][33] without discrete torsion, while fractional three-cycles consisting of components inherited from the torus plus exceptional divisors at orbifold singularities have been employed for Γ = Z 4 [34], Z 6 [35,33,36,37], Z ′ 6 [38][39][40][41][42]37] and Z 12−II [43] with a single Z 2 sector and Γ = Z 2 ×Z 2 [44,45], Z 2 ×Z ′ 6 [45][46][47] and Z 2 × Z 6 [45,[48][49][50] with discrete torsion with two Z 2 subgroups.…”
Section: Introductionmentioning
confidence: 99%